Manajemen Resiko Pengiriman Barang Online Menggunakan Sistem Pembayaran Cash on Delivery (COD) - Maria Oktarina; Iva Khoiril Mala (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This research discusses risk management for online goods delivery using the Cash on Delivery (COD) payment system. The COD system has become very popular in online buying and selling transactions, especially in Indonesia, because it offers convenience for customers in transactions. This research method uses a qualitative approach with literature analysis. The aim is to analyze the risk management of online goods delivery using the COD payment system and offer solutions to reduce the risks faced by sellers and customers. The results of this research show that the COD system also has several weaknesses, such as customer misunderstanding of the COD system and the absence of information on goods in their actual condition. The recommendation of this research is that it can increase customer loyalty, protection for couriers, digitalization in this case non-cash transaction payments like using QRIS.